Identification of the Ligands of TCRγδ by Screening the Immune Repertoire of γδT Cells From Patients With Tuberculosis - Li, Yuxia; Wang, Xinfeng; Teng, Da; Chen, Hui; Wang, Maoshui; Wang, Junling; Zhang, Jianmin; He, Wei (Frontiers in Immunology, 2019)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) infection is a serious threat to human health. γδT cells, which are characterized by major histocompatibility complex (MHC) nonrestriction, are rapidly activated and initiate anti-infectious immune responses in the early stages of Mtb infection. However, the mechanism underlying the recognition of Mtb by γδT cells remains unclear. In this study, we characterized the pattern of the human T-cell receptor (TCR) γδ complementary determinant region 3 (CDR3) repertoire in TB patients by using high-throughput immune repertoire sequencing. The results showed that the diversity of CDR3δ was significantly reduced and that the frequency of different gene fragments (V/J), particularly the V-segment of the δ-chain, was substantially altered, which indicate that TB infection-related γδT cells, especially the δ genes, were activated and amplified in TB patients. Then, we screened the Mtb-associated epitopes/proteins recognized by γδT cells using an Mtb proteome chip with dominant CDR3δ peptides as probes. We identified the Mtb protein Rv0002 as a potential ligand capable of stimulating the activation and proliferation of γδT cells. Our findings provide a further understanding of the mechanisms underlying γδT cell-mediated immunity against Mtb infection.